Hubungan Kecemasan Dengan Kadar Gula Darah Pada Pasien Diabetes Melitus - Tri Wijayanto; Widya Widya (LPPM Sikes Panca Bhakti Bandar Lampung, 2019)
Diabetes mellitus is a chronic progressive disease due to inadequate insulin production which results in the inability of the body to metabolize carbohydrates, proteins and fats which causes blood sugar levels in the body to rise above normal or hyperglycemia. One of the factors that influence blood sugar levels in the body is psychological stress. The purpose of this study was to find out the relationship between anxiety and blood sugar levels in patients with diabetes mellitus. This study uses a survey analytic method with a cross sectional approach. The population in this study were type 1 and type 2 diabetes mellitus patients with a sample of 81 people, and the sampling technique used was consecutive sampling. Data collection in this study used the observation sheet and HRS-A anxiety questionnaire. Test the statistics used by chi square. The results showed that the majority of respondents experienced severe anxiety as much as 64.2% and most respondents with high blood sugar levels> 200 mg / dL as much as 49.4%. There is a correlation between anxiety and blood sugar levels in patients with diabetes mellitus with p value 0.025 <α (0.05). The researcher gave recommendations to health workers to be able to provide health education to patients with diabetes mellitus about the process of diabetes mellitus and its management to reduce anxiety in patients with diabetes mellitus so that blood sugar levels can be controlled.